Accelerating Industrial Output Growth through Islamic Bank Decomposed Financing Optimization in Malaysia - Yasmin, Sadia; Ayaz, Mohammad; Ashraf, Muhammad Ather (iRASD Journal of Economics, 2022)
Literature shows two hypothesis ‘More finance more growth’ formed u-shape and ‘too much finance’ formed an inverted u-shape profile. Existing literature shows contradicting findings on finance growth nexus by taking only a single indicator of total financing, where financial expansion is detrimental to growth if it surpasses a specific threshold point. This gap is addressed in this study by decomposing Islamic financing into Islamic producer financing (IPF) and Islamic consumer financing (ICF) and its quadratic impact on industrial output growth in Malaysia. Autoregressive Distributive lag (ARDL) approach is applied over the period of 2008; Q1 to 2020; Q4 and, in order to visualize the effect of moderator to the nonlinear model, this study have used Dawson (2014) approach. This study demonstrates a u-shaped relationship between Islamic decomposed financing and sectoral output growth, highlighting that financial development starts to accelerate the growth, once it surpassed the calculated threshold point. With the intention to determine the right financial ceiling to restrict financial activity, threshold points are crucial to the regulators. Our findings imply that policymakers should not only enhance financing, but also improve the quality of the financial system for potential growth. This necessitates the simultaneous expansion and tightening of financial rules, as well as the attendant supervision and surveillance of financial activities, in order to preserve the integrity of finance growth nexus and avoid the ‘vanishing effect’ which may lead to the incidence of future economic crises. This study enriches the discussion on Islamic decomposed financing and the threshold effect to contribute to the economic growth of the country.